A Conceptual Framework for Enhancing Community Economic Independence through Capacity-Building Training and MSME Development - Mugi Lestari; Nestia Lianingsih (International Journal of Research in Community Services, 2026)
Building community economic independence is a strategic priority for achieving inclusive and sustainable development, particularly in developing regions where access to economic resources remains unequal. This study aims to develop a conceptual framework that integrates capacity-building training and micro, small, and medium enterprise (MSME) development as key drivers of community economic empowerment. The research employs a qualitative approach based on systematic literature review and conceptual synthesis to identify the main variables and relationships influencing economic independence. The findings indicate that capacity-building training plays a fundamental role in enhancing entrepreneurial capacity, including knowledge, skills, attitudes, and self-efficacy. This improvement subsequently contributes to MSME development, reflected in increased productivity, innovation, business growth, and financial performance. Furthermore, the relationship between capacity building and MSME development is strengthened by mediating factors such as social capital, mentoring, and institutional support, which facilitate collaboration and resource accessibility. External factors, including government policies, access to finance, and digitalization, also influence the effectiveness of these relationships. The study concludes that community economic independence is achieved through a comprehensive and integrated process involving internal capacity development and external ecosystem support. The proposed conceptual framework provides both theoretical and practical contributions by offering a systematic approach to designing sustainable community empowerment programs.